DNA isolation in processed goat meat products (tongseng) - Alfi Sophian (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2025)
DNA isolation from processed goat meat products (tongseng) was conducted to evaluate the quality of DNA extracted from these processed meat products. This study is intended to serve as a reference for similar research and to support the development of specific DNA detection assays using real-time PCR or authentication tests. The methodology employed in this study utilized standard testing procedures, with DNA quality parameters including concentration and purity measured using a nanophotometer at an A260/A280 ratio. The DNA isolation results are presented in Table 1 below. The table demonstrates that the isolated DNA concentration values ranged from 695,4 ng/µL to 708,4 ng/µL, with a mean concentration of 701,5 ng/µL. The purity values, measured at the A260/A280 ratio, ranged from 2,07 to 2,08, with an average purity value of 2,08. Based on the research findings, it can be concluded that the DNA isolated from processed goat meat food products exhibited good quality, as evidenced by the mean concentration value of 701,5 ng/µL and purity of 2,08. For future research, it is recommended to conduct similar studies on food products from other categories to obtain comprehensive information that can support species DNA identification assays or product authentication tests.